Judicial Trend in Nepalese Law of Contract: Current Perspective - Kalika, Satya Narayan (Management Dynamics, 2021)
This paper analyzes judicial decisions established by the Supreme Court of Nepal in relation to contractual disputes between 2023 and 2074 B.S. The earliest case of Dhruba Shumsher v. Nabaraj and the latest case of Tularatna Bajracharya v. Chetsundar Shrestha's legal heir Tara Shrestha Patrabansha are selected as basic information. The case laws related to contract law during the given period of more than five decades of modern Nepal have been collected, documented, selected and analyzed to understand the development trends of Nepalese law of contract. It helps us get a better and holistic current perspective on the existing and emerging issues and trends of Nepalese law of contract and guess the future voyage of this sector.